Outcome and quality of life after aorto-bifemoral bypass surgery - Abelha, Fernando J (BioMed Central, 2010)
BACKGROUND: Aorto-bifemoral bypass (AFB) is commonly performed to treat aorto-iliac disease and a durable long-term outcome is achieved. Most studies documenting beneficial outcomes after AFB have been limited to mortality and morbidity rates, costs and length of hospital stay (LOS). Few studies have examined the dependency of patients and how their perception of their own health changes after surgery. The aim of the present study was to evaluate outcome after AFB and to study its determinants. METHODS: This retrospective study was carried out in the multidisciplinary Post-Anaesthesia Care Unit (PACU) with five intensive care beds. Out of 1597 intensive care patients admitted to the PACU, 75 were submitted to infrarenal AFB and admitted to these intensive care unit (ICU) beds over 2 years. Preoperative characteristics and outcome were evaluated by comparing occlusive disease with aneurysmatic disease patients. Six months after discharge, the patients were contacted to complete a Short Form-36 questionnaire (SF-36) and to have their dependency in Activities of Daily Living (ADL) evaluated. Patient's characteristics and postoperative follow-up data were compared using Mann-Whitney U test, t test for independent groups, chi-square or Fisher's exact test. Patient preoperative characteristics were evaluated for associations with mortality using a multiple logistic regression analysis. RESULTS: The mortality rate was 12% at six months. Multivariate analysis identified congestive heart disease and APACHE II as independent determinants for mortality. Patients submitted to AFB for occlusive disease had worse SF-36 scores in role physical and general health perception. Patients submitted to AFB had worse SF-36 scores for all domains than a comparable urban population and had similar scores to other PACU patients. Sixty-six percent and 23% of patients were dependent in at least one activity in instrumental and personal ADL, respectively, but 64% reported having better general health. CONCLUSION: This study shows that congestive heart disease and APACHE II were risk factors for mortality after AFB surgery. Survivors who have undergone AFB perceive an improved quality of life although they are more dependent in ADL tasks and have worse scores in almost all SF-36 than the population to which they belong.